Severity of Escherichia coli bacteraemia is independent of the intrinsic virulence of the strains assessed in a mouse model. (23rd January 2012) - Landraud, L.; Jauréguy, F.; Frapy, E.; Guigon, G.; Gouriou, S.; Carbonnelle, E.; Clermont, O.; Denamur, E.; Picard, B.; Lemichez, E.; Brisse, S.; Nassif, X.
Abstract Extraintestinal pathogenic Escherichia coli (ExPEC) strains, a major cause of bacteraemia, typically belong to phylogenetic group B2 and express diverse accessory traits that contribute to virulence in mouse infection models. However, their high genomic diversity obscures the relationship between virulence factors and severity of infection in patients. In this study, we analysed concomitantly the strain's expression of virulence in a mouse model, genomic determinants and the clinical severity of infection in 60 bacteraemic patients. We show that bacterial virulence based on an animal model study and virulence factor determination is not correlated with pejorative outcome of E. coli human blood infections.